1989
DOI: 10.1007/bf00248283
|View full text |Cite
|
Sign up to set email alerts
|

Negative cortical DC shifts preceding and accompanying simple and complex sequential movements

Abstract: Negative cortical DC shifts preceding and accompanying the execution of four different motor tasks were analysed in 18 subjects (Ss): Repetitive flexions and extensions of the forefinger had to be performed either by the right (1) or the left (2) hand. This simple motor task was compared to a complex one in which flexions and extensions of forefinger and hand had to be alternated in a fixed sequence. The complex task had either to be performed by the right (3) or the left (4) hand. Thus, the four conditions di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 17 publications
3
24
1
2
Order By: Relevance
“…Conversely, movements by the left hand caused an increase of SPs in C4. These results were consistent with earlier studies [10,21]. Qualitatively the same and quantitatively similar effects of the side of the hand were present when subjects internally simulated the motor sequence.…”
Section: Eeg-studiessupporting
confidence: 92%
“…Conversely, movements by the left hand caused an increase of SPs in C4. These results were consistent with earlier studies [10,21]. Qualitatively the same and quantitatively similar effects of the side of the hand were present when subjects internally simulated the motor sequence.…”
Section: Eeg-studiessupporting
confidence: 92%
“…The first result is at variance with a number of previous stud ies (Benecke et al 1985;Kitamura et al 1993a;Simonetta etal. 1991), although there are also earlier studies that failed to find higher premovement RP amplitudes with sequential or complex movements (Lang et al 1988(Lang et al , 1989. It is noteworthy that the previously report ed effects concerned the terminal part of the RP, quanti fied by amplitude measures in the last 250 ms preceding EMG onset.…”
Section: Discussionmentioning
confidence: 91%
“…Whereas data obtained by Benecke et al (1985) and data from Simonetta etal. (1991) confirm this suggestion, Lang et al (1988; found that sim ple versus complex sequential movements and simulta neous versus sequential movements caused differential activity at the scalp only during movement execution but not before movement onset. These inconsistent findings might be interpreted as evidence that a movement being complex or sequential in nature may not be decisive for SMA involvement in movement preparation.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Studies on cortical DC shifts revealed that the amplitudes of potentials in the medial frontal cortex were larger when motor tasks involved (1) sequential movements, (2) memorized motor sequence, and (3) bimanual coordination [4,11]. Subsequent studies [28,34,36] extended these observations further. Of particular interest is the finding [35] that a large DC potential shifts were recorded when subjects were tapping different rhythms bimanually.…”
Section: Sma Neurons In Organizing Temporal Sequences Of Multiple Movmentioning
confidence: 88%